Sintering and oxidation behavior of HfB2-SiC composites from 0 to 30 vol% SiC between 1450 and 1800 K. Issue 2 (1st February 2019) - Piriou, Cassandre; Rapaud, Olivier; Foucaud, Sylvie; Charpentier, Ludovic; Balat-Pichelin, Marianne; Colas, Maggy
Abstract: Fully-dense HfB2 -SiC composites with controlled microstructure were obtained by Spark Plasma Sintering for 0–30 vol% SiC. Samples were then oxidized in a solar furnace at 1450, 1550 and 1800 K for 20 min under stagnant air. To complete this approach, the oxidation kinetics were followed by thermogravimetric analysis (TGA) for isothermal runs using the same conditions. Oxidized samples were characterized by X-ray diffraction, scanning electron microscopy and Raman mapping. The highest oxidation resistance, characterized by no mass evolution after 7 min exposure at 1800 K, was obtained for the sample containing 20 vol% SiC. At the same temperature, the oxidation kinetics of a composite with a lower amount of SiC (typically 10 vol%) was controlled by the diffusion of oxygen up to 10 µm in depth whereas a sample with 30 vol% SiC showed mass losses after 5 min exposure proving the presence of a non-protective oxide layer due to vaporization. Blisters of a glassy phase surrounded by hafnia were observed at the surface of all oxidized samples at 1800 K.